2014
DOI: 10.1101/lm.033589.113
|View full text |Cite
|
Sign up to set email alerts
|

Young and old Pavlovian fear memories can be modified with extinction training during reconsolidation in humans

Abstract: Extinction training during reconsolidation has been shown to persistently diminish conditioned fear responses across species. We investigated in humans if older fear memories can benefit similarly. Using a Pavlovian fear conditioning paradigm we compared standard extinction and extinction after memory reactivation 1 d or 7 d following acquisition. Participants who underwent extinction during reconsolidation showed no evidence of fear recovery, whereas fear responses returned in participants who underwent stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 37 publications
9
86
2
1
Order By: Relevance
“…The failure to “update” and interfere with the reconsolidation process using a nonpharmacological intervention observed in the present study is at odds with the findings of Agren, Engman et al (), Agren, Furmark, Eriksson, & Fredrikson (), Oyarzun et al (), Schiller et al (), and Steinfurth et al (), but consistent with prior negative results reported by Golkar et al (), Kindt and Soeter (), and Soeter and Kindt (). The explanation for the inconsistent findings across studies is not readily apparent, but seems unlikely to be due to procedural differences (see Golkar et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…The failure to “update” and interfere with the reconsolidation process using a nonpharmacological intervention observed in the present study is at odds with the findings of Agren, Engman et al (), Agren, Furmark, Eriksson, & Fredrikson (), Oyarzun et al (), Schiller et al (), and Steinfurth et al (), but consistent with prior negative results reported by Golkar et al (), Kindt and Soeter (), and Soeter and Kindt (). The explanation for the inconsistent findings across studies is not readily apparent, but seems unlikely to be due to procedural differences (see Golkar et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…These results are consistent with animal work using a similar protocol [34] and were replicated in later studies [60,61]. Recent findings suggest that, similar to young memories [59], older fear memories can also be updated and attenuated using extinction training after memory reactivation [62]. In addition, it has been shown that for labilization of fear memory to occur, new information has to be presented during reactivation (prediction error) [19] as demonstrated in animal work [16-18], supporting the notion that a function of reconsolidation is memory updating.…”
Section: Insights From Modifying Human Memoriessupporting
confidence: 84%
“…For instance, reconsolidation e ects have been observed with training-reminder intervals at 1d but not 8d (Forcato et al, 2013), 6d but not 20d (Coccoz et al, 2013), 2d and 7d, but not 14d or 28d (Milekic & Alberini, 2002), and 1d and 28d, but not 7d (Wichert et al, 2011). However, other studies have observed reconsolidation e ects for 'older' memory traces, with training-reminder intervals of 7d (Steinfurth et al, 2014), 14d (Nader et al, 2000a), 30d (Einarsson & Nader, 2012), and 60d (DÍbiec & LeDoux, 2004). A boundary condition of memory age also seems incompatible with the notion that expect, and what actually happens (Forcato et al, 2009;Pedreira et al, 2004;Morris et al, 2006;Rodriguez-Ortiz, 2005;Sevenster, Beckers, & Kindt, 2014).…”
Section: Cs = Plus/minusmentioning
confidence: 91%